1990
DOI: 10.1093/infdis/161.2.326
|View full text |Cite
|
Sign up to set email alerts
|

Decreased In Vitro Susceptibility to Zidovudine of HIV Isolates Obtained from Patients with AIDS

Abstract: This study tested isolates of human immunodeficiency virus, obtained before and after zidovudine therapy from 10 patients, for susceptibility to the drug in vitro. The isolates collected after therapy were less susceptible to zidovudine as assessed by replication in MT-2 cells and production of reverse transcriptase activity by infected mononuclear leucocytes in the presence of the drug. Furthermore, pretherapy isolates were sensitive to a range of zidovudine concentrations when 100% inhibition was used as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
33
0

Year Published

1992
1992
1997
1997

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(33 citation statements)
references
References 7 publications
0
33
0
Order By: Relevance
“…These viruses were found to contain up to five mutations (four amino acid substitutions) in the pol gene of HIV (16). Other studies have now confirmed that HIV regularly acquires resistance during AZT therapy (3,12,24) and that this resistance is associated with the presence of one or more of these mutations (3,15,17).…”
mentioning
confidence: 93%
“…These viruses were found to contain up to five mutations (four amino acid substitutions) in the pol gene of HIV (16). Other studies have now confirmed that HIV regularly acquires resistance during AZT therapy (3,12,24) and that this resistance is associated with the presence of one or more of these mutations (3,15,17).…”
mentioning
confidence: 93%
“…Experimental evidence showing the appearance, both in vitro and in vivo, of HIV-1 strains resistant to nucleoside analogues has been repeatedly reported (Larder and Kemp 1989;Larder et al, , 1991BOUCher et al, 1990;Land et al, 1990;Clair et al, 1991;Japour et al, 1991;Dianzani et al, 1992) but, so far, no data are available on the possibility of obtaining HIV-1 mutants resistant to proteinase inhibitors. Here we show that it is possible readily to select HIV-1 strains resistant to an inhibitor of HIV proteinase simply by growing the virus in the presence of the drug.…”
Section: Introductionmentioning
confidence: 99%
“…Monotherapy with nucleoside analogues or nonnucleoside reverse transcriptase (RT) inhibitors (NNRTIs) has, without exception, resulted in the emergence of drug-resistant virus. This may take only a matter of weeks with NNRTIs (Richman et al, 1993;Saag et al, 1993), or months to years in the case of the most studied nucleosides 3'-azido-3'-deoxythymidine (AZT, zidovudine), 2',3'-dideoxyinosine (ddI) and 2',3'-dideoxycytidine (ddC; Boucher et al, 1990;Fitzgibbon et al, 1992;Japour et al, 1991 ;Land et al, 1990;Larder et al, 1989;McLeod et al, 1992;Richman et al, 1990;Rooke et al, 1989;St. Clair et al, 1991).…”
Section: Introductionmentioning
confidence: 99%